IMPLEMENTATION OF THE COMPENSATION AND REWARD SYSTEM ON THE PERFORMANCE OF TEACHERS AND EMPLOYEES AT SMP "AL-ISLAM" KRIAN: SYSTEMATIC LITERATURE REVIEW (SLR) - Mufidah, Umroatul; Rindaningsih, Ida (Journal of Learning on History and Social Sciences, 2025)
Objective: This study aims to investigate the extent to which the implementation of compensation and reward systems enhances the performance of teachers and staff at SMP "Al-Islam" Krian, a highly favored school in Krian with over 1,000 students. Method: The research employed a Systematic Literature Review (SLR) methodology, analyzing 15 scientific articles to assess the relationship between compensation, reward systems, and performance improvements among educational staff. Results: The review of the 15 articles indicates that the implementation of compensation and reward systems has a significant positive impact on the performance of teachers and staff. These findings are contextualized with the real-life practices of compensation and reward systems at SMP "Al-Islam" Krian, highlighting its effectiveness in driving high productivity and motivation. Novelty: This study provides a comprehensive synthesis of existing literature linked to the specific case of SMP "Al-Islam" Krian, offering actionable insights for educational institutions to refine their compensation and reward strategies to optimize staff performance. It serves as a reference model for improving teacher and staff management practices across similar educational settings.